Atomic-level Ru-Ir mixing in rutile-type (RuIr)O2 for efficient and durable oxygen evolution catalysis - Yeji Park; Ho Yeon Jang; Tae Kyung Lee; Taekyung Kim; Doyeop Kim; Dongjin Kim; Hionsuck Baik; Jinwon Choi; Taehyun Kwon; Sung Jong Yoo; Seoin Back; Kwangyeol Lee (Nature Communications)
Abstract The success of proton exchange membrane water electrolysis (PEMWE) depends on active and robust electrocatalysts to facilitate oxygen evolution reaction (OER). Heteroatom-doped-RuOx has emerged as a promising electrocatalysts because heteroatoms suppress lattice oxygen participation in the OER, thereby preventing the destabilization of surface Ru and catalyst degradation. However, identifying suitable heteroatoms and achieving their atomic-scale coupling with Ru atoms are nontrivial tasks. Herein, to steer the reaction pathway away from the involvement of lattice oxygen, we integrate OER-active Ir atoms into the RuO2 matrix, which maximizes the synergy between stable Ru and active Ir centers, by leveraging the changeable growth behavior of Ru/Ir atoms on lattice parameter-modulated templates. In PEMWE, the resulting (RuIr)O2/C electrocatalysts demonstrate notable current density of 4.96 A cm−2 and mass activity of 19.84 A mgRu+Ir −1 at 2.0 V. In situ spectroscopic analysis and computational calculations highlight the importance of the synergistic coexistence of Ru/Ir-dual-OER-active sites for mitigating Ru dissolution via the optimization of the binding energy with oxygen intermediates and stabilization of Ru sites.